Strategi Pemasaran Produk Pada UMKM Sidayu Melalui Media Online (Facebook, Instagram, Dan Go Food (Gobiz) - Moh. Jufriyanto; Deny Andesta (Pusat Riset dan Inovasi Nasional, 2023)
Provision of knowledge and skills for MSME business actors needs to be carried out periodically to add insight into how the times, competitive conditions and changes in consumer behavior. The lack of marketing utilization through online media makes MSME actors do not have good competitiveness. Community service activities with Sidayu's MSME product marketing strategy through online media explain the importance of online marketing. In this activity explained some online media that can be used in marketing such as facebook, Instagram, go food (go biz). From the results of this activity, it is hoped that MSMEs can apply one of these online media as a means to increase marketing in order to increase sales and revenue.